2004
DOI: 10.1007/s10096-004-1123-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for detecting Blastocystis hominis

Abstract: In order to determine the comparative sensitivity of two methods of detecting Blastocystis hominis and to investigate the seasonality of infection with this enteric protozoan parasite, the present study was conducted. In each of two 3-month periods representing winter, spring (February-April) and summer (July-September), 500 routine stool submissions were examined for B. hominis using microscopy following either formol-ether concentration or in vitro culture using Jones' medium. The organism was detected in 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 13 publications
9
87
1
3
Order By: Relevance
“…An advantage of the in vitro culture method is that low numbers of Blastocystis can be cultured for use in other (e.g., genotypic and/or phenotypic) tests (Suresh and Smith, 2004). A previous study comparing detection methods for the diagnosis of Blastocystis infections revealed that out of 23 Blastocystis positive samples, 98 % and 52 % were positive using in vitro culture and PCR detection directly from the faeces, respectively (Termmathurapoj et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An advantage of the in vitro culture method is that low numbers of Blastocystis can be cultured for use in other (e.g., genotypic and/or phenotypic) tests (Suresh and Smith, 2004). A previous study comparing detection methods for the diagnosis of Blastocystis infections revealed that out of 23 Blastocystis positive samples, 98 % and 52 % were positive using in vitro culture and PCR detection directly from the faeces, respectively (Termmathurapoj et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies using Jones' medium supplemented with 10 % horse serum (Salim et al 1999 ;Leelayoova et al 2002 ;Suresh and Smith, 2004 ;Termmathurapoj et al 2004 ;Yakoob et al 2004 ;Yoshikawa et al 2004 c), only human faecal samples were screened for Blastocystis. However, several different types of media to cultivate Blastocystis have been reported, and it has been suggested that the usefulness of cultivation may depend on the reagents and protocols employed (Zaman and Khan, 1994 ;Leelayoova et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of xenic cultures, in which Blastocystis is grown in vitro with non-specific microorganisms, has been shown to be more sensitive in detecting Blastocystis but it is not commonly used in the diagnostic laboratory. [9][10][11] Molecular diagnosis by polymerase chain reaction (PCR) using the small subunit (SSU) ribosomal RNA gene is becoming more widely used for detection of enteric parasites. Although this technique is more costly, it is known to be more sensitive than the direct smear and xenic culture.…”
Section: Introductionmentioning
confidence: 99%